The Role of Islamic Religious Education as an Agent of Social Control in Addressing Moral Degradation in the Digital Era - Ikhlasul Ikhsan Ridho; Aniqoh (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The advancement of digital technology has significantly impacted students' lives, leading to moral degradation marked by indiscipline, social media misuse, declining courtesy, and weak self-control. These conditions demand that Islamic Religious Education (PAI) serves not only as a medium for transmitting religious knowledge but also as an agent of social control to shape character and reinforce moral values. This study aims to analyze PAI's role as a social control agent in addressing moral degradation in the digital era and to describe its function in student character formation. A qualitative case study approach was conducted at SMK YPE Sawunggalih Kutoarjo. Informants included PAI teachers, vice-principals for curriculum and student affairs, guidance counselors, and students. Data were gathered through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. Findings reveal that PAI functions as a social control agent through internalizing religious values, cultivating religious habits, teacher role-modeling, and strengthening school culture. Implemented strategies include Islamic-based digital literacy education, religious habituation, and character development via school programs. The results emphasize that successful moral development requires synergy among schools, families, and communities. This study reinforces PAI's relevance as a social control agent in tackling moral challenges in the digital age